Reimagining Islamic Political Philosophy for Pluralistic Democracies: Toward an Inclusive Sharia-Based Governance Model - Yoga Adi Prayogi; Andi Saryoko; Fadli Rais (International Forum of Researchers and Lecturers, 2024)
This research explores the integration of Islamic political philosophy with modern democratic frameworks, proposing an inclusive Sharia-based governance model that aligns Islamic values with contemporary democratic practices. The relationship between Islam and democracy is complex, with debates surrounding their compatibility and the potential conflicts between religious principles and democratic ideals. The study identifies key Sharia principles such as justice (adl), consultation (shura), and participatory equality, which can contribute to more inclusive and democratic governance systems. The literature review highlights both traditional and contemporary interpretations of Sharia in governance, focusing on how Sharia-based principles can support inclusivity, fairness, and public participation in pluralistic societies. A comparative analysis of traditional Islamic political models reveals that while these models often emphasize hierarchical structures and restrict participation, the proposed inclusive model encourages broader civic engagement, social justice, and equal representation for all citizens. The paper also examines the challenges of implementing such a model in modern democratic settings, addressing concerns over the integration of religious principles with secular governance frameworks. Furthermore, the study emphasizes the importance of adapting Sharia governance to the social and political realities of modern multicultural societies. The potential impact of the proposed model is significant, fostering fairer, more just, and inclusive political frameworks within pluralistic democracies. The paper concludes with recommendations for further research on the practical application of Sharia-based governance, particularly in diverse democratic contexts, and calls for standardized frameworks to ensure consistency and accountability in its implementation.